Achieving SDG 10: A global review of public service inclusion strategies for ethnic and religious minorities - Ghazala Mir; Saffron Karlsen; Winnie V. Mitullah; Upendra Bhojani; Benjamin Uzochukwu; Chinyere Okeke; Tolib Mirzoev; Bassey Ebenso; Naila Dracup; Gary Arthur Dymski; Doan Thi Thuy Duong; Bui Thi Thu Ha; et al. (United Nations Research Institute for Social Development (UNRISD), 2020)
Social inequalities are intensifying globally and widening divisions are linked to civil unrest. Disadvantaged ethnic and religious groups experience poor access to, representation in and outcomes from public services such as healthcare and education. As mechanisms for social participation and citizenship, public services are key to inclusive and sustainable societies. In this paper we present results of a systematic review on strategies for the inclusion of minority ethnic and religious communities, often neglected populations in term of sustainable development activity. We focus on four public service areas: education, health, local government and police services and identify evidence gaps. Our overall aim is to raise awareness and provoke debate, reflection and subsequently action towards the inclusion of disadvantaged ethnic and religious minorities within public services. Public service inclusion strategies were identified through a global evidence review and four country specific reviews conducted by the Socially Inclusive Cities Network - academics, NGOs, policy - makers and practitioners from India, Kenya, Nigeria, Vietnam and the UK. Published evidence was supplemented by country-based and international workshops involving over 230 relevant stakeholders. We specifically explored intersectional experience relating to gender, age and migration status. 56 publications were identified for the global review, mostly in health and education. Macro (social and political), meso (institutional) and micro (individual) arena were identified as three distinct but interconnected levels through which exclusion is operationalized. Three overarching frameworks appeared key to successful ethnic and religious inclusion initiatives: accounting for social context; multiple strategies for system reform; and collaboration with disadvantaged communities. Inclusion strategies that address macro, meso and micro level drivers of exclusion are needed to achieve the aspirations of SDG 10. Involving affected communities is key to their success.
Keywords: 330; SDG 10; ethnicity; religion; inclusion; public services